49.9k views
3 votes
If `f(x)=x^2-81` and `g(x)=(x-9)^(-1)(x+9)`, find `g(x)xxf(x)`.

2 Answers

2 votes

For this case we have the following fusions:


f (x) = x ^ 2-81\\g (x) = (x-9) ^ {- 1} * (x + 9)

We can rewrite g (x) as:


  1. g (x) = \frac {(x + 9)} {(x-9)}

According to the following power property:


a ^ {- 1} = \frac {1} {a ^ 1} = \frac {1} {a}

Also:

If we factor f (x) we have:


f (x) = (x + 9) (x-9)

We must find:


f (x) * g (x) = (x + 9) (x-9) * \frac {(x + 9)} {(x-9)}

We simplify common terms in numerator and denominator:


f (x) * g (x) = (x + 9) ^ 2

ANswer:


f (x) * g (x) = (x + 9) ^ 2

User Spade
by
6.4k points
3 votes

Answer:


g ( x ) * f ( x ) = ( x + 9 ) ^ 2

Explanation:

We are given the following two functions and we are to find
g(x) * f(x):


f(x)=x2-81


g(x)=(x - 9)^(-1) ( x + 9)


g(x)*f(x)=x^(-81) * (x+9)/(x-9)


g ( x ) * f ( x ) =((x+9)(x-9)(x+9))/(x-9)


g ( x ) * f ( x ) = ( x + 9 ) ( x + 9 )


g ( x ) * f ( x ) =( x + 9 ) ^ 2

User Crisboot
by
6.9k points